Robust separations in inductive inference - Fulk, M.A. (Foundations of Computer Science, 31st Symposium, 1990)
Results in recursion-theoretic inductive inference have been criticized as depending on unrealistic self-referential examples. J.M. Barzdin (1974) proposed a way of ruling out such examples and conjectured that one of the earliest results of inductive inference theory would fall if his method were used. The author refutes Barzdin's conjecture and proposes a new line of research examining robust separations which are defined using a strengthening of Barzdin's original idea. Preliminary results are presented, and the most important open problem is stated as a conjecture. The extension of this work from function learning to formal language learning is discussed.< >